Catastrophic Debris Flows in Kazbegi Mountain Area, Georgia – Use of Available Free Internet Information to Generate Conceptual Engineering Geological Model - M. Dostalik; J. Novotny; O. Kurtsikidze; G. Gaprindashvili (Lowland Technology International, 2020)
This paper presents how much valuable data is freelyavailable from the Internet to be efficiently used together withthe interpretation of internet maps and 3D visualizations toanalyse geological hazard of some areas in the sense ofconceptual engineering geological model generation. Theexample presented here is of the Kazbegi Mountain area inGeorgia near the border with Russia. The area in question isfamous for abundant debris flows with some of them being verycatastrophic and associated with melting glaciers. There weretwo tragic events in the recent past in the Dariali Gorge east ofthe Mkinvartsveri (Kazbegi) peak in 2014. Using the internetinformation together with geological experience it can be easilyanticipated what may happen in the future within the area due toslope movement hazards. Dangerous areas possibly to beaffected by debris flow (mud flow) in the future may be definedand thus cost-effectively provide the first step to avoidconstructions in these areas to eliminate the loss of human livesand destruction of property